Sustainable infrastructure : breakthroughs in research and practice (IGI Global, 2019)
"This book examines sustainable development through the lens of transportation, waste management, land use planning, and governance"-- Provided by publisher.
Keywords: City planning.; Ecovillages.; Infrastructure (Economics); elektronické knihy; electronic books